EFEKTIVITAS PENGGUNAAN METODE NUMERIK DALAM MENENTUAN TEGANGAN KERJA DIODA - Djeli Tulandi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
Working voltage diode can be determined based on the exponential form equation that states the relationship between the variable electrical current , voltage , and temperature diode electron charge . Determination of potential voltage diode can be done numerically using the method of looking for the root of the equation . There are several methods of searching for the roots of the equation graph method , the direct method , the two methods , regulation falsi method , Newton – Raphson method and the secant method.The purpose of this study is to show which method is most effective in determining the working voltage diode . The method used is descriptive analytic method . The results showed that the direct measurement method is a short procedure , obtain employment diode voltage v = 0.42216 volts at the 4th iteration , as well as the method of Newton - Raphson procedure is also very short because it only took 5 steps in determining the working voltage diode . The other method , the method for two , regulations falsi and secant method requires a longer iteration. Themethod is effective in determining the working voltage of diode 5selected method I sadirectmethod an dNewton-Raphson method